If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4c + -1) + -2 = 6c + 6 Reorder the terms: 2(-1 + 4c) + -2 = 6c + 6 (-1 * 2 + 4c * 2) + -2 = 6c + 6 (-2 + 8c) + -2 = 6c + 6 Reorder the terms: -2 + -2 + 8c = 6c + 6 Combine like terms: -2 + -2 = -4 -4 + 8c = 6c + 6 Reorder the terms: -4 + 8c = 6 + 6c Solving -4 + 8c = 6 + 6c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-6c' to each side of the equation. -4 + 8c + -6c = 6 + 6c + -6c Combine like terms: 8c + -6c = 2c -4 + 2c = 6 + 6c + -6c Combine like terms: 6c + -6c = 0 -4 + 2c = 6 + 0 -4 + 2c = 6 Add '4' to each side of the equation. -4 + 4 + 2c = 6 + 4 Combine like terms: -4 + 4 = 0 0 + 2c = 6 + 4 2c = 6 + 4 Combine like terms: 6 + 4 = 10 2c = 10 Divide each side by '2'. c = 5 Simplifying c = 5
| -8m+5m=-9 | | -3v=-4x | | 10d-6=1d-15 | | 4/3h=12 | | 3(x+5)=5(x-2) | | 6=b+8+b | | 6v^2=24 | | y=-(2/3)x+3 | | 0/1110 | | -3(1+5x)-8=94 | | -77=-5(7m-4)-2(m-7) | | 8x-9=1+x | | r-(-36)=5 | | 6a(-5+3)-14=6a-12+25 | | -3(1+5x)-7=94 | | 7.8k-2.14=-42.7 | | Ax-7=box+4 | | m-1/6-4m+5/6=0 | | -5(y-7)=3y-29 | | -x^2+21x-104=0 | | 2.3w-(7)+8.1-3w=0 | | 0.2x+3.4+0.8x=4 | | ((20+20i)x^2)+((-3.82+21.66i)x)+(12.5-21.65i)=0 | | m+(-20)=(-12) | | 2.3w-7+8.1-3w=0 | | -46=-5(2-2x)-2(-6-7x) | | P+6/3=10/8 | | 10-7n=-31 | | 4x+1+4x+1+3x=90 | | 4x+1-5x=5 | | 6x=10x-4 | | 1/8(47-7)=x |